Midlife Dietary Intakes of Monounsaturated Acids, n–6 Polyunsaturated Acids, and Plant-Based Fat Are Inversely Associated with Risk of Cognitive Impairment in Older Singapore Chinese Adults. Issue 4 (25th December 2019) - Jiang, Yi-Wen; Sheng, Li-Ting; Pan, Xiong-Fei; Feng, Lei; Yuan, Jian-Min; Pan, An; Koh, Woon-Puay
ABSTRACT: Background: Previous studies have shown inconsistent results for the relation between dietary fat intake and cognitive function in the elderly. Furthermore, prospective studies on this topic among the Chinese population are scarce. Objectives: We aimed to examine the association between midlife dietary fat intake and risk of cognitive impairment in the elderly. Methods: Prospective cohort analysis was conducted among 16, 736 participants from the Singapore Chinese Health Study. Dietary information was assessed by a validated FFQ at baseline (1993–1998) when participants aged 45–74 y (mean: 53.5; SD: 6.22). Cognitive impairment was identified using the Singapore modified Mini-Mental State Examination at the third follow-up visit (2014–2016) when participants aged 61–96 y (mean: 73.2; SD: 6.41). Multivariable logistic regression models were used to calculate ORs and 95% CIs. Results: Cognitive impairment was presented in 2397 participants. When substituted for total carbohydrate, dietary fat intake was inversely related to cognitive impairment (OR comparing extreme quartiles: 0.80; 95% CI: 0.67, 0.94; P -trend = 0.003). The OR (95% CI) comparing extreme quartiles of specific dietary fats was 1.08 (0.89, 1.31; P -trend = 0.51) for SFAs, 0.80 (0.64, 0.99; P -trend = 0.02) for MUFAs, 0.84 (0.72, 0.99; P -trend = 0.02) for PUFAs, 0.92 (0.77, 1.09; P -trend = 0.49) for n–3 PUFAs, and 0.83 (0.70, 0.98; P -trend = 0.01) for n–6 PUFAs. An inverse association was found for plant-based fat (OR: 0.84; 95% CI: 0.72, 0.98; P -trend = 0.02), but not for animal-based fat (OR: 0.96; 95% CI: 0.81, 1.15; P -trend = 0.76). When substituted for SFAs, the OR (95% CI) was 0.77 (0.61, 0.97; P -trend = 0.02) for MUFAs and 0.82 (0.70, 0.95; P -trend = 0.003) for PUFAs. Conclusions: We found that substitution of total carbohydrate or SFAs with MUFAs and PUFAs, particularly n–6 PUFAs, was related to a lower risk of cognitive impairment in elderly Chinese participants. In addition, an inverse association with cognitive impairment was found for plant-based fat.